2-Hydroxy-4-Methylselenobutanoic Acid Promotes Follicle Development by Antioxidant Pathway - Xu, Shengyu; Dong, Yanpeng; Chen, Sirun; Liu, Yalei; Li, Zimei; Jia, Xinlin; Briens, Mickael; Jiang, Xuemei; Lin, Yan; Che, Lianqiang; Zhuo, Yong; Li, Jian; et al. (Frontiers in Nutrition, 2022)
Selenium (Se) is assumed to promote the follicle development by attenuating oxidative stress. The current study was developed to evaluate the effects of dietary 2-hydroxy-4-methylselenobutanoic acid (HMSeBA) supplementation on the follicle development in vivo and on the function of ovarian granulosa cells (GCs) in vitro. Thirty-six gilts were randomly assigned to fed control diet (CON), Na2SeO3 diet (0.3 mg Se/kg) or HMSeBA diet (0.3 mg Se/kg). The results showed that HMSeBA and Na2SeO3 supplementation both increased the total selenium content in liver and serum compared with control, while HMSeBA increased the total selenium content in liver compared with Na2SeO3 group. HMSeBA tended to increase the total selenium content in ovary compared with control. HMSeBA and Na2SeO3 supplementation both increased the weight of uteri in gilts at the third estrus. Moreover, HMSeBA supplementation down-regulated the gene expression of growth differentiation factor-9 (GDF-9) and bone morpho-genetic protein-15 (BMP-15) in cumulus-oocyte complexes (COCs). HMSeBA supplementation decreased malondialdehyde (MDA) content in serum, liver and ovary, increased activity of T-AOC in liver, TXNRD in ovary and GPX in serum, liver and ovary, while up-regulated the liver GPX2, SOD1 and TXNRD1, ovarian GPX1 gene expression. In vitro, HMSeBA treatment promoted GCs’ proliferation and secretion of estradiol (E2). HMSeBA treatment increased the activity of T-AOC, T-SOD, GPX, TXNRD and decreased MDA content in GCs in vitro. Meanwhile, HMSeBA treatment up-regulated SOD2 and GPX1 gene expression in GCs in vitro. In conclusion, HMSeBA supplementation is more conducive to promoting follicle development by antioxidant pathway.